Optimalisasi Pendapatan Asli Desa melalui Tata Kelola dan Inovasi BUMDes: Studi Kasus Desa Mojorejo, Mojokerto - Putra, Aditya Ferdana; Pratiwi, Silvi; Putri, Dheby Ayu Juliana; Purnomo, Wahyu; Maghfiroh, Lailatul (Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines strategies to optimize Village Original Revenue (PADes) in Mojorejo Village, Mojokerto, through the management and innovation of Village-Owned Enterprises (BuMDes) and economic diversification based on local potential. This study investigates how to optimize Village Original Revenue (PADes) in Mojorejo Village, Mojokerto District, by improving the Village-Owned Enterprises (BUMDes) and integrating local potential into the economy. This research stems from the fact that sustainable village fiscal independence by utilizing local resources and assets is essential. This research was conducted through a descriptive qualitative approach with data collection methods such as observation, and interviews. The contribution of BUMDes, problems faced, and opportunities for the advancement of the village economy were revealed through thematic analysis. The results showed that tourism, particularly Bukit Bunga Mojorejo (BBM), will be the largest contributor to village revenue by 2023, reaching 37%. However, issues such as low community participation, limited management capacity, and poor digital promotion continue to hinder village business management. Entrepreneurship training, tourism communities, bamboo crafts and agritourism sector development are solutions to these problems. According to this research, innovative local potential-based management and working together can increase village revenue and strengthen the village economy independently and sustainably. The key to successful village development as a competitive local economic growth center is a participatory and transparent approach.